Effects of Dietary Fermented Flammulina velutipes Mycelium on Performance and Egg Quality in Laying Hens - Lee, Sang-Bum; Im, Jintaek; Kim, Seon-Ku; Kim, Youn-Chil; Kim, Min-Jeung; Lee, Jae-Seung; Lee , Hong-Gu (International Journal of Poultry Science, 2014)
This study was conducted to evaluate the effect of dietary Flammulina velutipes mycelium (FFVM) fermented with Bacillus subtilis A8-8 and Klebsiella sp. Sc on the performance of laying hens including the egg quality, the pathogenic bacterial (Escherichia coli and Salmonella spp.) counts in caecal contents and the NH3 production in excreta. One hundred eighty Hy-Line Brown hens were fed one of six diets, including a corn-soybean meal based control diet and control diets supplemented with FFVM at 1, 2, 3, 4, or 5% (n = 30 per experimental group). During the 5 week experimental period, laying hen performance, egg quality, pathogenic bacteria number in caecum and fecal NH3 gas production were estimated. Although there were no significant differences in egg production, feed intake and feed conversion among experimental groups, egg weight was significantly increased in the 1 and 3% FFVM groups compared with the control diet group (p